Cover Feature: Entropy‐Driven Cooperativity in the Guest Binding of an Octaphosphonate Bis‐cavitand (Chem. Eur. J. 14/2020). Issue 14 (30th January 2020) - Shimoyama, Daisuke; Haino, Takeharu
Abstract : An octaphosphonate biscavitand showed an uncommon entropy‐driven positive cooperativity in the guest binding. The water molecules formed the cluster‐like assemblies at the two cavities of the biscavitand in chloroform. The guest binding broke the hydrogen‐bonded water molecules, which is responsible for the entropy‐driven cooperativity in the multiple guest binding. More information can be found in the Full Paper by D. Shimoyama and T. Haino on page 3074 .